Recurrent miscarriage in a novel translocation 7:9 carriers with no infertility - Siewert, Susana Elfrida (2017)
A balanced translocation between the short arm of chromosome 7 and the long arm ofchromosome 9 was observed in a pedigree of three carriers (proband, his daugtherand first cousin). In this study, the proband and first cousin have no infertilityproblems, they had phenotypically normal progeny but shows recurrent miscarriage.Cytogenetic analysis of metaphase chromosomes was performed, the karyotype of theproband carrier was determined as 46, XY, t(7;9)(7pter 7p12;9qter9q34::7p12 7qter). The study of this family is important because to ourknowledge there have not previous report with the same translocation, and it has beentransmitted through generations. In conclusion, the most striking finding was the nonexistence of unbalanced offspring after detecting a structural chromosomeabnormality in the parents. To understand the cytogenetic and clinical significance ofthis case the authors discuss the possible causes of recurrent miscarriage. Detection ofchromosomal abnormalities in spontaneous abortion materials is very important toclarify the causes of loss of pregnancy. The evaluation of the incidence of segregationproducts of balanced translocation in sperm nuclei of carriers can be evaluated byFISH, using the proper combination of probes, and will give patients more accurategenetic advice and helps to personalize the reproductive risk in male carriers ofbalanced translocation 7:9.